SPECIAL RULES OF MITIGATION OF PUNISHMENT IN CASE OF THE CONCLUSION OF THE PRE-TRIAL COOPERATION AGREEMENT, AT THE SPECIAL PROCEDURE OF FOR THE TRIAL AND AT THE SHORTENED ORDER OF INQUIRY - T. Nepomnyashchaya; A. Tebenkov (Правоприменение)
The subject. The article analyzes the rules for the appointment of punishment in the case of a pre-trial cooperation agreement, with a special procedure for the trial and with a shortened procedure of conducting inquiry, regulated by art. 62 of the RF Criminal Code “Turning out a Sentence when Mitigating Circumstances Exist”. The authors give an answer to two questions: 1) Does the legal nature of these institutions correspond to the legal nature of mitigating circumstances; 2) Is it advisable to consolidate in a one article of the law different legal regulations.Methodology. Authors use such researching methods as analysis and synthesis, formally legal, comparative legal.Results. Rules for the appointment of punishment in the conclusion of a pre-trial cooperation agreement, stipulated by the pt. 2, 4 of art. 62 of the RF Criminal Code, regulate not the order of accounting for mitigating circumstances, but the legal consequences associated with the promotion of a person, which concluded and executed a pre-trial cooperation agreement, that does not correspond to the legal nature of the pt. 1, 3 of art. 62 of the RF Criminal Code.The legal nature of the rules for the appointment of punishment, established in pt. 5 of art. 62 of the RF Criminal Code, also does not correspond to the legal nature of the rules for the imposition of punishment in the presence of mitigating circumstances, because mitigation of punishment occurs on criminal procedural grounds, which are not mitigating circumstances.Conclusions. In authors opinion, fastening in art. 62 of the RF Criminal Code of three independent rules for the imposition of punishment, namely, the rules for the imposition of punishment in the presence of mitigating circumstances (pt. 1, 3 of art. 62 of the Criminal Code), at the conclusion of a pre-trial cooperation agreement (pt. 2, 4 of art. 62 of the Crim-inal Code), with a special order of the trial and a shortened procedure for conducting an inquiry (pt. 5 of art. 62 of the Criminal Code) is unreasonable and inexpedient, because these rules have a different legal nature.Formalized limits of mitigation imposed at all parts of art. 62 of the Criminal Code of RF, are not connected with each other.Rules for the imposition of punishment in the conclusion of a pre-trial cooperation agreement, with a special procedure for the trial and a shortened procedure for conducting inquiry have to be deleted from art. 62 of RF Criminal code and have to be consolidated at separate articles of the Criminal Code.